PERSEPSI PETANI TERHADAP USAHATANI PADI VARIETAS CILAMAYA MUNCUL DAN CIHERANG DI KECAMATAN PALAS KABUPATEN LAMPUNG SELATAN - Firuza Filardhi; Tubagus Hasanuddin; Suarno Sadar (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2015)
This research aims to: knowing farmers perceptions, knowing whether there are differences in the perception, knowing what factors are most associated with the perception, knowing the level of income of rice farmers Cilamaya Muncul and Ciherang. The study was conducted in the village Bumi Restu and the village Bumi Daya, Sub-District Palas, South Lampung regency. The total sample size of 86 respondents were drawn by proportional random sampling method. The data was collected from November 2013 – januari 2014. The research used was  survey method. Inter-variable relationships were tested using analysis Partial Kendal correlation test, and perception differences examined with Mann-Whitney test. The result of research show that: the farmers’ perception toward the Cilamaya Muncul and Ciherang rice varieties is in the level of relative advantage which is more profitable, the level of conformity is quite appropriate which is not complicated, the of try is quite easy and the level of research is quite easy to be researched. There was the difference perception between the farmers of Cilamaya Muncul and Ciherang at Bumi Restu village toward Cilamaya Muncul rice varieties and at Bumi Daya village toward Ciherang rice varieties. The factors that associated with the perception of farmers on Cilamaya Muncul rice varieties in Bumi Restu village were farmers knowledge and social interaction, in Bumi Daya village there were knowledge of farmers, social interactions and needs. Meanwhile the factors related to the perception of farmers on the Ciherang rice varieties in Bumi Restu village and Bumi Daya village was a necessity. Cilamaya Muncul rice varieties and Ciherang rice varieties in Palas, Southern Lampung District in overall was profitable. Key words : ciherang rice, cilamaya muncul rice, perception, farm income